Penggunaan Sosial Media Marketing Sebagai Upaya Meningkatkan Jumlah Pengunjung di Blitar Park - Muhammad Teguh Himawan; Siti Ning Farida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the continually evolving digital era, social media plays a crucial role in influencing consumer behavior and decisions, particularly in the tourism sector. Blitar Park, as a recreational destination in Blitar, East Java, experiences significant impacts from the penetration of social media. With diverse facilities and activities, Blitar Park must leverage social media as an effective marketing tool to attract more visitors. Social media has become a vital source of information, and understanding how social media content influences visitor decisions is key. This research identifies effective types of social media content in capturing the attention and interest of the public to visit Blitar Park. The study employs a qualitative method with observations and literature reviews to delve into the meanings and characteristics of social media usage at Blitar Park. Insight analysis from social media platforms provides an overview of visitor responses to published content. The research findings indicate that Blitar Park has successfully utilized social media, but a decline in content publication consistency led to a performance decrease in certain months. Consistency in publication, diverse content types, and more active engagement with visitors are essential elements for enhancing the effectiveness of marketing through social media.